Comparison of Commercial Poultry Semen Extenders Modified for Cryopreservation Procedure in the Genetic Resource Program of Czech Golden Spotted Hen - Petričáková, Kristýna; Janošíková, Martina; Ptáček, Martin; Zita, Lukáš; Savvulidi, Filipp Georgijevič; Partyka, Agnieszka (Animals, 2022)
Spermatozoa cryoconservation represents an important strategy for partial in vitro or rescue programs designed for threatened livestock populations. The procedure for the semen cryopreservation of the Czech Golden Spotted Hen was proposed due to the lower fertilization rate of poultry semen compared to mammalian species. The aim of this study was to compare commercial extenders designed for liquid storage preservation with the use of a predefined cryoprotectant, and, thus, to propose an important tool for the procedure of the semen cryopreservation of the Czech Golden Spotted Hen. Ejaculates were sampled from four roosters during five semen collection days. The samples were frozen in Poultry media®, Raptac® and NeXcell® extenders supplemented with a 9% N-methylacetamide (NMA) cryoprotectant. Sperm parameters of the total motility (MOT; %), plasma membrane and acrosome intactness (PAI; %), plasma membrane damage (%), acrosome damage (%) and cells with plasma membrane and acrosome damage (%) were assessed using a mobile mCASA analyzer and flow cytometer after the cryopreservation of the insemination doses (IDs). For Poultry media® (PAI = 51.11%; MOT = 23.58%) and Raptac® (PAI = 52.04%; MOT = 23.13%) extenders with the addition of an NMA cryoprotectant, the comparable results were detected after thawing. For NexCell® media, the results were poor (PAI = 7.07%; MOT = 3.83%). Our results indicated two extenders suitable for the cryopreservation procedure, with the applied modification.
Keywords: cryoprotectant; sperm evaluation; rooster; spermatozoa; flow cytometry; gene reserve